The Cambridge companion to John Clare - Houghton-Walker, Sarah (Cambridge University Press, 2024)
The fascinations of John Clare's life are manifold. A labouring-class poet and naturalist, he was lionised in the early 1820s but spent his final decades incarcerated in asylums. In this Companion leading scholars illuminate Clare's rich life and writing, situating each within a range of critical contexts. Essays rooted in discourses as diverse as ecocriticism, aesthetics, religion, health, and time are accompanied by explorations of the construction of the idea (including the self-identity) of Clare through writing and images. The collection also traces influences upon Clare, and considers the ways in which he has influenced subsequent poets in turn. The volume includes a chronology and an invaluable guide to further reading, and provides students with a firm grounding in Clare's writings and his critical reception: this is an indispensable guide to the poet and his work.
Includes bibliographical references (pages 257-267) and index
Keywords: Clare, John / 1793-1864 / Criticism and interpretation; Religious poetry, English / History and criticism; Pastoral poetry, English / History and criticism